If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 4 = 8n + -1 Reorder the terms: 4 + 3n = 8n + -1 Reorder the terms: 4 + 3n = -1 + 8n Solving 4 + 3n = -1 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 4 + 3n + -8n = -1 + 8n + -8n Combine like terms: 3n + -8n = -5n 4 + -5n = -1 + 8n + -8n Combine like terms: 8n + -8n = 0 4 + -5n = -1 + 0 4 + -5n = -1 Add '-4' to each side of the equation. 4 + -4 + -5n = -1 + -4 Combine like terms: 4 + -4 = 0 0 + -5n = -1 + -4 -5n = -1 + -4 Combine like terms: -1 + -4 = -5 -5n = -5 Divide each side by '-5'. n = 1 Simplifying n = 1
| 4(2w+3)+2(3+w)= | | 4(w-6)=3(a+1) | | 7x+13=2x+8 | | -21+7y=9x | | 58-2+7=8x | | 3a+34b= | | 0.1x=.2(2+x) | | 2(b+5)+6b=5b+2b+1 | | 4x-13x+10=0 | | -10h=-6(4+3h) | | .5xn=.333 | | 6x+2y=16.60 | | 4(5)-4x=4 | | -4k(k+6)-(9k-6)=-14k | | 3x+2.5x=60 | | P=2(1.08)t | | 4.9t^2+17.9t+5=0 | | 12.8*0.25= | | X-90=4x | | 5a=7+8a | | 4x-2(x-4)=-6+4x+10 | | (10x^2+30x)=(2x^2-30x-75) | | -2x+5(-2x-6)=18 | | 3-(6s-15)=4s+8 | | 20x^2+25x+75=0 | | 3x+3=x-18 | | -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 |